The Potential of Microbial Symbionts Macrotermes gilvus Hagen Termite Gut as Degrading Agents of Cellulose in Bioethanol Production - Dewi Susilowati; Niken Subekti; Siti Harnina Bintari (Biosaintifika: Journal of Biology & Biology Education)
Water hyacinth is a potential feedstock for bioethanol production because of their high cellulose. The microbial symbionts of the Macrotermes gilvus termite’s gut have a high endoglucanase enzyme activity. This research was aimed to analyze the pH, temperature and agitation effects towards cell density, endoglucanase enzyme activity and reducing sugar, and to determine the effective optimum condition that can produce maximum reducing sugar. This research used central composite design (CCD) with the total number of run was . The independent variables were including pH (5.9, 6.4, 7.0, 7.6, 8.0), temperature (30 0C, 33 0C, 37 0C, 41 0C, 44 0C) and agitation (90 rpm,114 rpm, 150 rpm,185 rpm, 210 rpm), with six replications at central points. Parameters measured were cell density, endoglukanase enzyme activity and reducing sugar, thus analyzed by the statistical software package MINITAB 18.0. The Student’s t-test result showed the primary sequence influencing cell density as pH ˃ agitation ˃ temperature and towards endoglucanase enzyme activity and reducing sugar as pH ˃ temperature ˃ agitation, P ˂ 0.05. The maximum reducing sugar (60.13 ± 3.16 mmolL-1) was obtained at pH 6.95, temperature 37 0C and agitation 150 rpm. The results of this research can be used to explore the more potential microbial symbionts of the Macrotermes gilvus Hagen termite’s gut.